Pure copper or copper alloy powder for additive manufacturing

CN117858776BActive Publication Date: 2026-10-30JX NIPPON MINING & METALS CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202280055171.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-09-01
Filing Date
2022-08-30
Publication Date
2026-10-30
Estimated Expiration
2042-08-30

AI Technical Summary

Technical Problem

但是,有可能因成型时的热传导而导致覆膜变质,有可能无法反复使用粉末

Benefits of technology

[0019]根据本发明,在基于激光束方式的增材制造中,能够提高在该增材制造中使用的纯铜或铜合金粉末的激光吸收率,并且能够降低成型物内的氧浓度。由此,能够期待能够抑制成型物的机械强度、电导率等特性降低。另外,即使利用低输出功率的激光束,也能够使纯铜或铜合金粉末充分地熔融,能够期待减轻对激光器的负荷。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004700609340000111
    Figure BDA0004700609340000111
Patent Text Reader

Abstract

To provide a pure copper or copper alloy powder for additive manufacturing based on a laser beam method, which can improve laser absorptivity and can reduce oxygen concentration in a molded article. A pure copper or copper alloy powder formed with an oxide coating film, wherein the oxide coating film contains carbon, and the ratio of oxygen concentration to carbon concentration (oxygen concentration / carbon concentration) is 5 or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to pure copper or copper alloy powder for additive manufacturing. Background Technology

[0002] In recent years, there have been attempts to use metal 3D printing technology to create metal parts with complex shapes and three-dimensional structures that are considered difficult to form. Metal 3D printing is also known as additive manufacturing (AM). One of its methods is as follows: a thin layer of metal powder is deposited on a substrate to form a metal powder layer. Based on two-dimensional data, a laser beam or electron beam is selectively scanned on the metal powder layer to melt it and then solidify it. Then, a new thin layer of powder is deposited on it, and the same laser beam or electron beam is scanned to melt it and then solidify it. This process is repeated to create metal parts with complex shapes.

[0003] As additive manufacturing products (also simply called molded products), efforts are being made to utilize pure copper and copper alloys, which possess excellent electrical and thermal conductivity. In this case, additive manufacturing is performed by irradiating pure copper or copper alloy powder with a laser beam. However, due to the low laser absorption rate of pure copper and copper alloys (the laser absorption rate of pure copper is 10%–20%) and their high thermal conductivity, resulting in significant heat loss, the powder cannot be fully melted at typical laser output power, posing a challenge for additive manufacturing. Furthermore, to melt the pure copper or copper alloy powder, long-term irradiation with a high-power laser has been considered. However, this approach suffers from high laser load and low productivity.

[0004] Patent Documents 1 and 2 disclose a technique in which an oxide coating is formed by heating atomized copper powder in an oxidizing atmosphere to improve laser absorption. Patent Documents 1 and 2 represent excellent techniques for improving laser absorption through oxide coating. However, sometimes slag (copper oxide) forms during the forming process, which remains unmelted and ultimately creates voids (pores) in the additively manufactured product, thus reducing its relative density.

[0005] Patent documents 3 and 4 describe a technique of coating metal powder with an organic compound to improve laser absorption. Patent documents 3 and 4 represent excellent techniques for improving laser absorption by utilizing an organic compound coating. However, the coating may deteriorate due to heat conduction during molding, potentially preventing the powder from being reused repeatedly.

[0006] Patent document 5 describes the following technology: using copper alloy powder obtained by adding a specified amount of chromium (Cr) to copper (Cu) as molding powder, the thermal conductivity is reduced compared to pure copper, thus making it easier to mold.

[0007] Existing technical documents

[0008] Patent documents

[0009] Patent Document 1: Japanese Patent Application Publication No. 2018-178239

[0010] Patent Document 2: Japanese Patent Application Publication No. 2020-186429

[0011] Patent Document 3: Japanese Patent Application Publication No. 2018-199662

[0012] Patent Document 4: Japanese Patent Application Publication No. 2020-190008

[0013] Patent Document 5: Japanese Patent Application Publication No. 2019-44260 Summary of the Invention

[0014] The problem that the invention aims to solve

[0015] The present invention aims to provide a pure copper or copper alloy powder for use in laser beam-based additive manufacturing, wherein the pure copper or copper alloy powder can improve laser absorption rate and reduce oxygen concentration in the formed product.

[0016] means for solving problems

[0017] One aspect of the present invention is a pure copper or copper alloy powder, wherein the pure copper or copper alloy powder is formed with an oxide coating, characterized in that the oxide coating contains carbon, and the ratio of oxygen concentration to carbon concentration (oxygen concentration / carbon concentration) is 5 or less.

[0018] Invention Effects

[0019] According to the present invention, in laser beam-based additive manufacturing, the laser absorption rate of the pure copper or copper alloy powder used in the additive manufacturing process can be increased, and the oxygen concentration in the formed article can be reduced. Therefore, it is expected that the reduction in properties such as mechanical strength and electrical conductivity of the formed article can be suppressed. Furthermore, even using a low-output-power laser beam, the pure copper or copper alloy powder can be sufficiently melted, which is expected to reduce the load on the laser. Detailed Implementation

[0020] When pure copper or copper alloy parts are formed by additive manufacturing using a laser beam, the low laser absorptivity of copper prevents sufficient heat input, resulting in incomplete melting of the powder. Furthermore, the high thermal conductivity of copper limits the complete melting of the formed area. Therefore, efforts have been made to improve laser absorptivity by oxidizing the copper (Patent Documents 1-2), etc.

[0021] While the above measures significantly improve laser absorption, in high oxygen concentrations, oxygen tends to remain in the molded product as oxides, leading to a decrease in the product's mechanical strength, electrical conductivity, and other properties. The inventors conducted in-depth research on this problem and arrived at the following insight: By forming an oxide coating on pure copper or copper alloy powder, and ensuring that this oxide coating contains an appropriate amount of carbon, oxygen combines with carbon during molding, removing it as carbon monoxide or carbon dioxide. This allows for the improvement of laser absorption while simultaneously reducing the oxygen concentration in the molded product.

[0022] Based on the above understanding, an embodiment of the present invention is a pure copper or copper alloy powder, wherein the pure copper or copper alloy powder is formed with an oxide coating, characterized in that the oxide coating contains carbon, and the ratio of oxygen concentration to carbon concentration (oxygen concentration / carbon concentration) is 5 or less. Here, the carbon concentration and oxygen concentration are each by weight.

[0023] By adjusting the carbon and oxygen concentrations to the aforementioned ratio range, carbon combines with oxygen during molding, thereby effectively removing oxygen and carbon in the form of carbon monoxide or carbon dioxide, reducing the impact of oxide residues on the molded product. It should be noted that the oxide coating in this application is not limited to oxide coatings intentionally formed by heating pure copper or copper alloy powder, but can also be an oxide coating formed naturally under atmospheric conditions.

[0024] When the oxygen concentration / carbon concentration ratio is greater than 5, the possibility of oxygen (oxides, etc.) remaining in the molded article increases, which may cause adverse effects such as reduced strength and electrical conductivity of the molded article. The oxygen concentration / carbon concentration ratio is preferably 1 or less. On the other hand, when the carbon concentration ratio is too high, carbon remains as an impurity; therefore, the oxygen concentration / carbon concentration ratio is preferably 0.01 or higher. By keeping the oxygen concentration / carbon concentration ratio within the above-mentioned range, oxygen and carbon can be effectively removed during molding in the form of carbon monoxide and carbon dioxide.

[0025] In this embodiment, the oxygen concentration of the pure copper or copper alloy powder is 5000 ppm by weight or less, preferably 3000 ppm by weight or less, and more preferably 1500 ppm by weight or less. On the other hand, the oxygen concentration is preferably 50 ppm by weight or more, and more preferably 100 ppm by weight or more. When an oxide coating is formed on the surface of the pure copper or copper alloy powder, the laser absorption rate can be improved. On the other hand, if the oxygen concentration increases during molding, it may cause a decrease in various properties. Therefore, considering both improving the laser absorption rate and suppressing the decrease in the properties of the molded product, it is effective to limit the oxygen concentration in the pure copper or copper alloy powder to a certain amount.

[0026] The carbon concentration can be adjusted by taking oxygen concentration into account, and the carbon concentration is preferably 100 ppm by weight or more, more preferably 150 ppm by weight or more, and particularly preferably 200 ppm by weight or more. When the carbon concentration is insufficient relative to the concentration of oxygen, which exists mainly in the form of oxides, oxygen cannot be sufficiently removed during molding, and sometimes the oxygen concentration of the final molded article cannot be sufficiently reduced. On the other hand, when the carbon concentration is too high relative to oxygen, carbon remains in the molded article, resulting in a decrease in relative density. Therefore, the carbon concentration is preferably 5000 ppm by weight or less, more preferably 3000 ppm by weight or less, and particularly preferably 1000 ppm by weight or less.

[0027] In this embodiment, it is preferable that the pure copper or copper alloy powder with an oxide coating contains heat-resistant carbon that is not easily decomposed even at high temperatures. Examples of heat-resistant carbon include amorphous carbon and graphite. It is believed that the presence of heat-resistant carbon can improve laser absorption rate and improve formability even during the heating process until the powder melts. In addition, it can reduce the thermal conductivity of the powder and suppress heat diffusion. Organic materials that are not heat-resistant tend to disappear easily during the molding process, making it difficult to suppress heat dissipation. On the other hand, by providing a heat-resistant structure, carbon can suppress heat dissipation even during the molding process.

[0028] One method for analyzing the bonding state (structure) of carbon is Raman spectroscopy. Raman spectroscopy can confirm the bonding state of atoms on a surface, and in particular, it allows for detailed analysis of carbon bonding. When using Raman spectroscopy to determine the bonding state of pure copper or copper alloy powder in this embodiment, the Raman shift is 1000 cm⁻¹. -1 ~2000cm -1 The maximum scattering intensity value within the range is within the Raman displacement of 1300 cm. -1 ~1700cm -1 The maximum scattering intensity was confirmed within the specified range. The maximum scattering intensity occurred at a Raman shift of 1300 cm⁻¹. -1 ~1700cm -1 Within a certain range, it can be determined that it has a graphite structure.

[0029] When analyzing the CuLMM spectrum of the pure copper or copper alloy powder of this embodiment using XPS (X-ray photoelectron spectroscopy), the maximum peak intensity preferably exists in the binding energy range of 569 eV to 571 eV. In the case of elemental copper, the maximum peak intensity occurs below the binding energy of 568 eV. In contrast, the maximum peak intensity of cuprous oxide (I) and copper oxide (II) occurs in the binding energy range of 569 eV to 571 eV. By using copper in the form of copper oxide, the laser absorption rate becomes better, which may improve the formability. Therefore, the copper on the powder surface preferably exists in the form of cuprous oxide (I) or copper oxide (II).

[0030] In this embodiment, the thickness of the oxide coating formed on the surface of pure copper or copper alloy powder is preferably 5 nm or more and 500 nm or less. If the oxide coating is too thick, the relative density of the final additive manufacturing product will decrease during laser-based additive manufacturing. On the other hand, if the oxide coating is too thin, the increase in laser absorption is insufficient, and the pure copper or copper alloy powder may not be completely melted. By adjusting the thickness of the oxide coating formed on the surface of pure copper or copper alloy powder, a high-density additive manufacturing product can be obtained.

[0031] In this embodiment, the average particle size D of the pure copper or copper alloy powder is preferably... 50 The median particle size is between 10 μm and 150 μm. The average particle size D is used to determine this. 50 With a particle size of 10μm or larger, the powder is less prone to flying during molding, making powder handling easier. On the other hand, through the average particle size D... 50 With a particle size below 150 μm, it is easy to manufacture high-precision additive manufacturing products. In this specification, the average particle size D... 50 It refers to the average particle size when the cumulative value in the particle size distribution obtained through image analysis is 50%.

[0032] As the pure copper powder used in this embodiment, pure copper with a purity of 3N (99.9% by weight) or higher is preferably used. Furthermore, as the copper alloy powder used in this embodiment, copper alloy powder containing 80% by weight or more, 85% by weight or more, 90% by weight or more, 95% by weight or more, or 99% by weight or more of copper is preferably used. Additionally, as the alloying element, one or more of Al, Cr, Fe, Ni, Nb, P, Si, Zn, and Zr are preferably used.

[0033] Additively manufactured products made using the pure copper or copper alloy powder of this embodiment can be expected to have excellent physical properties such as high electrical conductivity. It is generally believed that when the oxygen concentration in an additively manufactured product is greater than 200 ppm by weight, oxides remain in the additively manufactured product, resulting in decreased electrical conductivity and deteriorated properties as a molded product. However, when using the pure copper or copper alloy of this embodiment, the oxygen concentration in the molded product can be reduced to below 200 ppm by weight, and high electrical conductivity can be expected.

[0034] Next, the method for manufacturing pure copper or copper alloy powder according to this embodiment will be described.

[0035] First, prepare the required amount of pure copper or copper alloy powder. It is preferable to use pure copper or copper alloy powder with an average particle size D. 50The median particle size is 10 μm to 150 μm of pure copper or copper alloy powder. The target particle size can be obtained by sieving. Pure copper or copper alloy powder can be produced using an atomization method, but the pure copper or copper alloy powder in this embodiment can also be pure copper or copper alloy powder produced by other methods, and is not limited to pure copper or copper alloy powder produced by this method.

[0036] Next, in order to form an oxide coating on the surface of pure copper or copper alloy powder, heating can be performed in the atmosphere. The oxygen concentration and film thickness can be adjusted by the heating temperature and heating time; for example, the heating temperature can be set to 70°C to 200°C, and the heating time can be set to 2 hours to 48 hours. In addition, the oxide coating can also be intentionally formed by heating, or an oxide coating that forms naturally in the atmosphere can be utilized.

[0037] Then, carbon is incorporated into the pure copper or copper alloy powder with the oxide coating. There are no particular limitations on the method for incorporating carbon; for example, carbon black can be mixed with pure copper powder using a ball mill or mortar. Alternatively, carbon can be incorporated into the pure copper powder by heating a liquid organic compound in an inactive atmosphere. Alternatively, a graphite film can be formed on the pure copper powder using CVD (chemical vapor deposition). Examples of suitable carbon-containing materials for incorporating carbon into pure copper or copper alloy powder with the oxide coating include: carbon black, coal tar, pitch, coke, and organic compounds. In this case, the carbon concentration (content) needs to be adjusted according to the oxygen concentration. Through the above methods, pure copper or copper alloy powder with the desired oxygen and carbon concentrations can be obtained.

[0038] The evaluation methods used in this disclosure are described.

[0039] (Regarding average particle size D) 50 )

[0040] Manufacturer: MicrotracBEL

[0041] Device Name: MT3300EXII

[0042] Measurement method: Laser diffraction (volume standard)

[0043] Solvent: Pure water

[0044] Refractive index: 1.33

[0045] (Regarding the oxygen concentration in the powder)

[0046] Manufacturer: LECO

[0047] Device Name: TCH600

[0048] Analytical method: Inactive gas melting method

[0049] Sample volume to be measured: 1g

[0050] Number of measurements: Set to 2 times, and use the average value as the concentration.

[0051] (Regarding the carbon concentration in the powder)

[0052] Manufacturer: LECO

[0053] Device Name: TCH600

[0054] Analytical method: Inactive gas melting method

[0055] Sample volume to be measured: 1g

[0056] Number of measurements: Set to 2 times, and use the average value as the concentration.

[0057] (Film thickness of oxide coating)

[0058] The thickness of the oxide coating is determined by Auger electron spectroscopy (AES) while excavating the powder surface at a certain sputtering rate. The value is calculated based on the time taken until no oxygen is detected and the sputtering rate. The detection is performed at two randomly selected points from a single particle; the values ​​in this example represent their average.

[0059] Manufacturer: Nippon Electronics Co., Ltd.

[0060] Device Name: AES (JAMP-7800F)

[0061] Filament current: 2.22A

[0062] Probe voltage: 10kV

[0063] Probe current: 1.0 × 10 -8 A

[0064] Probe diameter: approximately 500 nm

[0065] Sputtering rate: 7.2 nm / min (converted to SiO2)

[0066] (About XPS)

[0067] The presence of copper oxide can be confirmed using XPS. By analyzing the LMM spectrum of copper using XPS, the presence of peaks in the range of 569 eV to 570 eV indicates the presence of copper oxide.

[0068] Manufacturer: ULVAC Co., Ltd.

[0069] Device Name: 5600MC

[0070] (Regarding carbon bonding)

[0071] The presence of the graphite structure could be confirmed using Raman spectroscopy. The maximum scattering intensity value, determined by Raman spectroscopy, is located at a Raman shift of 1300 cm⁻¹. -1 ~1700cm -1 Within a certain range, it can be determined that a graphite structure exists.

[0072] Manufacturer: Ranishow

[0073] Device Name: invia

[0074] (Regarding laser absorption rate)

[0075] Typical laser-based molding uses fiber lasers with a wavelength of approximately 1060 nm. Therefore, the reflectivity at a wavelength of 1060 nm is measured and the laser absorption rate is calculated.

[0076] Manufacturer: Shimadzu Corporation

[0077] Device Name: Spectrophotometer (MPC-3100, using powder holder)

[0078] Measurement wavelength: 300mm~1500mm

[0079] Slit width: 20nm

[0080] Reference: BaSO4

[0081] Measurement of physical property value: reflectance

[0082] Absorption rate (%) = 1 - (Reflectance (%))

[0083] (Oxygen concentration and relative density in the molded part)

[0084] Pure copper or copper alloy powder is heated to its melting point and then cooled to create a simulated molded object. The oxygen concentration in this molded object is then measured. The method for measuring the oxygen concentration can be the same as that used for measuring the oxygen concentration of the powder described above. Furthermore, the Archimedean density of the simulated molded object is measured, and the relative density is calculated by dividing the measured Archimedean density by the theoretical density of pure copper or the copper alloy.

[0085] Example

[0086] (Example 1)

[0087] The average particle size (D) to be produced by atomization 50Pure copper powder with a thickness of 35.0 μm was used as the metal powder. This pure copper powder was heated at 150°C for 24 hours in atmospheric air to form an oxide coating on its surface. Next, the pure copper powder with the oxide coating was placed in a mortar, and carbon black was added and mixed to achieve an oxygen concentration / carbon concentration ratio of approximately 0.40. The oxygen concentration, carbon concentration, and laser absorptivity of the pure copper powder prepared in this manner were measured. The prepared pure copper powder was then heated to its melting point to melt it, and then cooled to prepare a simulated molded object. The oxygen concentration, carbon concentration, and relative density of the obtained simulated molded object were measured. The results are shown in Table 1. As shown in Table 1, the pure copper powder of Example 1 was confirmed to have a high laser absorptivity. Furthermore, the simulated molded object prepared using the pure copper powder of Example 1 was confirmed to have a low oxygen concentration and a high relative density.

[0088]

[0089] (Example 2)

[0090] The average particle size (D) to be produced by atomization 50 Pure copper powder with a thickness of 35.0 μm was used as the metal powder. This pure copper powder was heated at 150°C for 24 hours in atmospheric air to form an oxide coating on its surface. Next, the pure copper powder with the oxide coating was placed in a mortar, and carbon black was added and mixed so that the oxygen concentration / carbon concentration ratio was approximately 0.80. The oxygen concentration, carbon concentration, and laser absorptivity of the pure copper powder prepared in this manner were measured. The prepared pure copper powder was then heated to its melting point to melt it, and then cooled to prepare a simulated molded object. The oxygen concentration, carbon concentration, and relative density of the obtained simulated molded object were measured. The results are shown in Table 1. As shown in Table 1, the pure copper powder of Example 2 was confirmed to have a high laser absorptivity. Furthermore, the simulated molded object prepared using the pure copper powder of Example 2 was confirmed to have a low oxygen concentration and a high relative density.

[0091] (Example 3)

[0092] The average particle size (D) to be produced by atomization method 50Pure copper powder with a particle size of 35.0 μm was used as the metal powder. Next, the pure copper powder was immersed in a solution diluted with toluene to contain 5% by weight of coal tar. After immersion, the pure copper powder removed from the solution was heated in an inactive atmosphere. The oxygen concentration, carbon concentration, and laser absorptivity of the resulting pure copper powder were measured. The results are shown in Table 1. As shown in Table 1, the pure copper powder of Example 3 was confirmed to have a high laser absorptivity (the laser absorptivity of pure copper is 10%–20%). It should be noted that in Example 3, no simulated molded object was prepared, but as in Examples 1 and 2, the pure copper powder exhibited a high laser absorptivity and a low oxygen concentration, thus suggesting minimal oxide formation. It is also expected that the simulated molded object will achieve the same effects as in Examples 1 and 2.

[0093] (Comparative Example 1)

[0094] The average particle size (D) to be produced by atomization method 50 Pure copper powder with a thickness of 35.0 μm was used as the metal powder. This pure copper powder was heated at 150°C for 24 hours in atmospheric air to form an oxide coating on its surface. It should be noted that in Comparative Example 1, carbon, such as carbon black, was not mixed in. For the pure copper powder prepared in this manner, the oxygen concentration, carbon concentration, and laser absorptivity were measured. Furthermore, the prepared pure copper powder was heated to its melting point to melt it, and then cooled to prepare a simulated molded object. The oxygen concentration, carbon concentration, and relative density of the obtained simulated molded object were measured. The results are shown in Table 1. As shown in Table 1, it was confirmed that the simulated molded object prepared using the pure copper powder of Comparative Example 1, which did not intentionally contain carbon, had a high oxygen concentration.

[0095] Industrial practicality

[0096] According to the present invention, in laser beam-based additive manufacturing, it is possible to improve the laser absorption rate and reduce the oxygen concentration in the formed product. This is expected to suppress the decline in properties such as mechanical strength and electrical conductivity of the additively manufactured product. Furthermore, it is expected to reduce the load on the laser device. The pure copper or copper alloy powder of this embodiment is particularly useful as a pure copper or copper alloy powder for additive manufacturing.

Claims

1. A pure copper or copper alloy powder, wherein the pure copper or copper alloy powder has an oxide coating, wherein, The oxide coating contains carbon, and the oxygen concentration to carbon concentration ratio (oxygen concentration / carbon concentration) is less than 5. The carbon has a graphite structure. The oxide coating thickness is greater than 5 nm and less than 500 nm. The average particle size D of the pure copper or copper alloy powder is... 50 That is, the median particle size is above 10μm and below 150μm.

2. The pure copper or copper alloy powder according to claim 1, wherein, The oxygen concentration is below 5000 ppm by weight.

3. The pure copper or copper alloy powder according to claim 1, wherein, The carbon concentration is above 100 ppm by weight.

4. The pure copper or copper alloy powder according to claim 2, wherein, The carbon concentration is above 100 ppm by weight.

5. The pure copper or copper alloy powder according to any one of claims 1 to 4, wherein, When measuring the pure copper or copper alloy powder using Raman spectroscopy, the Raman shift was 1000 cm⁻¹. -1 ~2000cm -1 The maximum scattering intensity value exists within the Raman shift of 1300 cm⁻¹. -1 ~1700cm -1 Within the range.

6. The pure copper or copper alloy powder according to any one of claims 1 to 4, wherein, When analyzing CuLMM spectra using XPS, the maximum peak intensity exists in the binding energy range of 569 eV to 571 eV.

7. The pure copper or copper alloy powder according to any one of claims 1 to 4, wherein, The pure copper or copper alloy powder is pure copper or a copper alloy containing more than 80% by weight of copper.

8. The pure copper or copper alloy powder according to any one of claims 1 to 4, wherein, The pure copper or copper alloy powder is used for laser beam-based additive manufacturing applications.

Citation Information

Patent Citations

  • Copper powder, manufacturing method therefor, and manufacturing method of solid molded article

    JP2018178239A

  • Cosmetic product

    JP2018199662A

  • Copper alloy powder, heat treatment method for multilayer shaped structure, method for producing copper alloy shaped structure, and copper alloy shaped structure

    JP2019044260A

  • Copper powder having excellent laser light absorbency

    JP2020186429A

  • Organic surface-coated copper-based powder, laminated article comprising copper-based material formed with organic surface-coated copper-based powder, method for manufacturing laminated article, and various metallic components

    JP2020190008A